Breast Implant–associated Anaplastic Large Cell Lymphoma in Colombia: Report of a Multidisciplinary National Registry - Ossa Gomez, Carlos Andrés; Duque, Alejandro; Huertas Motta, Ramiro; Fidalgo, Ana Maria; Rivas Taffur, Giovanna; Caicedo Mallarino, José Joaquín; Mantilla Duran, William Armando; Abello Polo, Virginia; Echeverri, Carolina (Revista Colombiana de Hematología y Oncología, 2022)
Background: An estimated 43,390 breast augmentation surgeries (86,780 implants) and 1486 breast implant reconstructions are performed annually in Colombia, representing the second-most breast surgery destination in South America, the fourth in the western hemisphere, and the fifth country worldwide. No previous reports have evaluated the incidence of breast implant–associated anaplastic large cell lymphoma (BIA-ALCL) epidemiology or outcomes in a Hispanic population. Published data on the incidence of this disease in Colombia are unknown; therefore, a National Joint Multidisciplinary Committee was developed between the Colombian scientific societies of Mastology, Plastic Surgery, Hemato-Oncology, and the Invima (The National Food and Drug Surveillance Institute) to track national cases of BIA-ALCL. Materials and Methods: We performed a retrospective review (survey-based study) of historical cases since 2011–2019, and a prospective collection of all patients with a confirmed World Health Organization diagnosis of BIA-ALCL identified in a newly established National Registry of BIA-ALCL. The trial was approved by Institutional Review Board (IRB).